APPLICATION OF STANDARD COSTS TO CONTROL PRODUCTION COSTS FOR NIRWANA BROWN SUGAR PRODUCTS: (Study : UD. Gula Nirwana Desa Dayu - Blitar) - Melinda Oky Pangesti; Rumanintya Lisaria Putri (Fakultas Ekonomi Universitas 45 Surabaya, 2018)
UD Gula Nirwana is a small medium business that reprocesses coconut sugar, cane sugar and white sugar into brown sugar or vegetable sugar, UD. Gula Nirwana produces every day, so that makes it an active effrort to produce brown sugar needed by the community in general. Therefore this business can continue when production costs can be reduced one of them is by using standard costs in calculating production costs. Determination of standard costs can be an alternative in planning and controlling production costs. This study aims to see how the standard cost method applies to UD Gula Nirwana. Standard costs are costs that are used as guidelines before the production process takes place. When standard costs have been determined and the actual costs are known at the end of the production period, the standard costs and actual costs rather than produce variance or difference. Based on the calculation that the comparative analysis of standard costs with actual costs, it can be concluded that in the production of brown sugar, the difference in the cost of production of profitable raw materials and factory overhead costs is still stable and the difference in labor is still a difference in limits even though it is not profitable